Selective Exposure Media Sosial Pada Ibu dan Perilaku Anti Sosial Anak - Setiyaningsih, Lian Agustina; Fahmi, Muhammad Hanif; Molyo, Priyo Dari (Jurnal Komunikasi Nusantara, 2021)
Abstract: The rapid development of technology has accelerated the adaptation to the use of technology. Especially the use of technology on social media that affects family communication, namely on behavior change. The impact depends on the selective exposure (duration and frequency). Mothers often experience commodification and are identified with groups that are not well literate in the use of social media. So that raises the hypothesis of the effect of selective exposure on mothers on their children's anti-social behavior. This quantitative descriptive study uses a quasi-experimental method by providing initial insights to respondents. As many as 82 respondents of mothers in Malang Raya were involved in this study with the criteria of productive age, have children aged 5-12 years and have used social media for about 3 years. The sampling technique uses purposive sampling because it refers to the above criteria. This study conducted a test of reliability and validity, while in data analysis using linear regression and t test. The results of this study indicate that mothers are positioned under the control of technology which brings a trickle effect so that it can create a negative effect on children. Selective social media exposure to mothers has a significant effect 56,7% and correlation 1,568. Anti-social behavior is generated in form of refusal to interact with environment, aggressive, impulsive, quiet and has no regrets making mistakes. Keywords: selective exposure; social media; mother; anti-social; children Abstrak: Perkembangan teknologi yang cepat menyebabkan percepatan adaptasi atas penggunaan teknologi. Terutama pemanfaatan teknologi pada media sosial yang berpengaruh terhadap komunikasi keluarga yakni pada perubahan perilaku. Dampak yang ditimbulkan bergantung pada selective exposure (durasi dan frekuansi). Ibu sering mengalami komodifikasi dan diidentikan dengan golongan yang tidak terliterasi dengan baik dalam penggunaan media sosial. Sehingga memunculkan hipotesis adanya pengaruh selective exposure pada ibu terhadap perilaku anti sosial anaknya. Penelitian dekriptif kuantitatif ini menggunakan metode kuasi eksperimen dengan memberikan wawasan awal kepada responden. Sebanyak 82 responden ibu di Malang Raya terlibat dalam penelitian ini dengan kriteria usia produktif, memiliki anak usia 5-12 tahun dan telah menggunakan media sosial kurang lebih 3 tahun. Teknik sampling menggunakan purposive sampling karena merujuk pada kriteria di atas. Penelitian ini melakukan uji reliabilitas dan validitas, sedangkan dalam analisis data menggunakan regresi linier dan uji t. Hasil penelitian ini menunjukkan ibu diposisikan di bawah kendali teknologi yang membawa trickle effect sehingga mampu menciptakan pengaruh negatif terhadap anak. Selective exposure media sosial pada ibu berpengaruh signifikan sebesar 56,7% dengan korelasi sebesar 1,568. Perilaku anti sosial yang ditimbulkan berupa penolakan berinteraksi dengan lingkungan, agresif, impulsif, pendiam serta tidak memiliki penyesalan ketika berbuat kesalahan. Kata kunci: selective exposure; media sosial; ibu; anti sosial; anak